2009
DOI: 10.1086/597585
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance and Outcome of Nosocomial Acquisition of Spontaneous Bacterial Peritonitis in Patients with Liver Cirrhosis

Abstract: Nosocomial SBP has a poorer outcome than community-acquired SBP. The resistance to third-generation cephalosporins for gram-negative organisms, which are more common in nosocomial cases of SBP than in community-acquired cases of SBP, adversely affects the outcome of SBP in patients with liver cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
184
6
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(224 citation statements)
references
References 13 publications
26
184
6
8
Order By: Relevance
“…Recent studies have reported an increasing prevalence of extended-spectrum β-lactamase-producing bacteria and multiresistant gram-positive bacteria such as Enteroccocus faecium or MRSA [52] . In fact, bacteria isolated in nosocomial SBP are frequently resistant to β-lactams (33%-78%), and this is associated with a low success rate in a significant proportion of nosocomial SBP [53][54][55][56] , which are being treated with third generation cephalosporins, amoxicillin/clavulanic acid or quinolones.…”
Section: Treatment Of Nosocomial Sbpmentioning
confidence: 99%
“…Recent studies have reported an increasing prevalence of extended-spectrum β-lactamase-producing bacteria and multiresistant gram-positive bacteria such as Enteroccocus faecium or MRSA [52] . In fact, bacteria isolated in nosocomial SBP are frequently resistant to β-lactams (33%-78%), and this is associated with a low success rate in a significant proportion of nosocomial SBP [53][54][55][56] , which are being treated with third generation cephalosporins, amoxicillin/clavulanic acid or quinolones.…”
Section: Treatment Of Nosocomial Sbpmentioning
confidence: 99%
“…Common Gram-negative bacteria such as Escherichia coli and other coliforms such as Klebsiella spp. have been reported to be causative agents in at least 50% of cases [6][7][8][9][10]. Other causative organisms reported have included pneumococci, streptococci and miscellaneous Gram-positive and other Gram-negative organisms [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an increasing number of cases of SBP due to extended spectrum b-lactamase (ESBL)-producing E. coli, K. pneumonia have been reported in Asia [8][9][10][11] and Europe [12][13][14][15][16]. Some risk factors for SBP caused by ESBL-producing bacteria Enterobacteriaceae have been identified including the in-hospital acquisition of infection [10][11][12][13][14][15], long-term norfloxacin prophylaxis [13], use of blactams within the last 3 months [13], and infection by multiresistant bacteria in the last 6 months [13].…”
mentioning
confidence: 99%
“…Some risk factors for SBP caused by ESBL-producing bacteria Enterobacteriaceae have been identified including the in-hospital acquisition of infection [10][11][12][13][14][15], long-term norfloxacin prophylaxis [13], use of blactams within the last 3 months [13], and infection by multiresistant bacteria in the last 6 months [13]. ESBLproducing strains are resistant not only to third-generation cephalosporins, amoxicillin-clavulanic acid but also to quinolones and trimethoprim-sulfamethoxazole [13].…”
mentioning
confidence: 99%
See 1 more Smart Citation